KNOWLEDGE ON DIABETES AND ITS RELATED FACTORS AMONG TYPE -2 DIABETIC PATIENTS IN SAMBALPUR, ODISHA - TRUPTI PRADHAN; CHANDRASHREELENKA (The Journal of Research ANGRAU, 2022)
Increased awareness among population is a major factor for the prevention of diabetes and its complications and related metabolic disorders. Knowledge is the most important element of awareness that need to be studied in various population groups in specific cultural contexts. On this backdrop the present study was undertaken to explore knowledge regarding diabetes mellitus (DM) among type 2 diabetes mellitus (T2DM) patients in Sambalpur district of Odisha during the year 2021.The study also investigated association between knowledge with different socio-demographic characteristics of the patients. Three hundred (300) diabetic patients of District Head Quarter Hospital, Sambalpur, Odisha were included in the study. Knowledge regarding diabetes was judged by using a self administered questionnaire. The scores were analysed against the variables to determine the association of knowledge with socio demographic variables.Out of those 300 respondents maximum responds (63%) had fair knowledge followed by good and poor (26% and 11%) knowledge respectively. Significant association was found between age, area of residence, family income, family type and duration of diabetes with diabetes knowledge. No significant association was found withgender, education, occupation, age of onset of disease, and family history of diabetes. Awareness related to all the aspects of diabetes mellitus need to be increased among the diabetic patients for better control of the disease and its complications.